TEACHING CHILDREN IN THREE LEARNING STYLES - SUYUNOVA DIYORA BAKHTIYOR KIZI; ZIYAYEVA MAKHBUBA FAZLIDDINOVNA (International Journal of Innovations in Engineering Research and Technology, 2021)
This article describes three main learning styles and using them to pupils from the elementary classes. Since they give an effective result and lighten the process of learning.